Chemical and biological investigations of Dillenia indica Linn. - Most. Nazma Parvin, Mohammad S. Rahman, Mohammad S. Islam and Mohammad A. Rashid (Bangladesh Pharmacological Society, 2009)
A total of four compounds namely, lupeol (1), betulinaldehyde (2), betulinic acid (3) and stigmasterol (4) were isolated from the stem extract of Dillenia indica Linn. The structures of the isolated compounds (1-4) were established by extensive spectroscopic studies. The crude methanolic extracts and its n-hexane, carbon tetrachloride, dichloromethane and chloroform soluble partitionates demonstrated weak antimicrobial activity against a wide range of Gram-positive and Gram-negative bacteria and fungi. The extractives revealed significant cytotoxic activity when tested by brine shrimp lethality bioassay. In addition, the extractives exhibited significant free radical scavenging activity when compared with ascorbic acid.